The Impact of Learning Agility and the Work Environment during Work from Home on Teacher Performance - Sintha Wahjusaputri; Hupron Fadilah (STAI Hubbulwathan Duri, 2022)
This research aims to identify, describe and analyze the influence of learning agility and work environment during work from home (WFH) on teacher performance at The Cikeas Nature School. Research methods through quantitative research approach with survey methods fill out online questionnaires with respondents from all teachers from Playgroup, kindergarten, elementary, junior high and high school level with 56 all teachers at state elemenatary school in Cikeas, Bogor. Data collection techniques by conducting interviews, questionnaires and documentation. Data analysis techniques use multiple linear regressions. The results of the study that agilty learning had a significant effect on teacher performance with results greater than critical grades (6,974 2,005), X2 significantly affected Y with results (thitung) greater than critical values (2,208 2,005). The results of the R2 test from Learning Agility and Work Environment during WFH against teacher performance by 69.9%. This means that the contribution of other factors (other than learning agility and work environment during WFH) to teacher performance is only 30.1%. This research proves that there are positive effects of learning dexterity on performance, there are positive influences of the work environment on teacher performance.